Machine learning applied to threat intelligence - Arboleda Díaz, Joseph Nikolay; Medina Ruiz, Leslie Tatiana (Escuela Colombiana de Ingeniería Julio Garavito, 2017)
Introducir los términos de Machine Learning e investigar los diferentes algoritmos que se pueden desarrollar actualmente, con herramientas como Weka y Cuckoo Sandbox, además de conocer diferentes aplicaciones teóricas y prácticas de los diferentes aspectos de la Seguridad Informática, con el fin de conocer aquellas necesidades aún no cubiertas por el Machine Learning. También se dará a conocer el procedimiento para la creación de una Red Neuronal Artificial, con la capacidad de clasificar archivos en tres tipos de familia de malware, producto final del proyecto.

Introduce the terms of Machine Learning and investigate the different algorithms that can be developed today, with tools such as Weka and Cuckoo Sandbox, in addition to knowing different theoretical and practical applications of the different aspects of Computer Security, with the weekend at the same time not covered by Machine Learning. The procedure for the creation of an Artificial Neural Network was also announced, with the ability to classify files in three types of malware families, the final product of the project.
Keywords: Aprendizaje Automático; Seguridad informática; Machine Learning; Informatic security